2001
DOI: 10.1093/glycob/11.4.37r
|View full text |Cite
|
Sign up to set email alerts
|

Glycobiology of sperm-egg interactions in deuterostomes

Abstract: The process of fertilization begins when sperm contact the outermost egg investment and ends with fusion of the two haploid pronuclei in the egg cytoplasm. Many steps in fertilization involve carbohydrate-based molecular recognition between sperm and egg. Although there is conservation of gamete recognition molecules within vertebrates, their homologues have not yet been discovered in echinoderms and ascidians (the invertebrate deuterostomes). In echinoderms, long sulfated polysaccharides act as ligands for sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
94
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 87 publications
3
94
0
Order By: Relevance
“…Protein-carbohydrate interactions play important roles in many aspects of reproduction across a wide range of animal species. Such interactions are vital for sperm-egg fusion in both invertebrates and vertebrates (Rosati et al 2000;Mengerink and Vacquier 2001;Intra et al 2006), with egg glycoproteins acting as primary sperm receptors in many species. Moreover, recent studies have shown that protein-carbohydrate interactions are directly /Df(2L)ED611 (M) males in each of four replicates is shown.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-carbohydrate interactions play important roles in many aspects of reproduction across a wide range of animal species. Such interactions are vital for sperm-egg fusion in both invertebrates and vertebrates (Rosati et al 2000;Mengerink and Vacquier 2001;Intra et al 2006), with egg glycoproteins acting as primary sperm receptors in many species. Moreover, recent studies have shown that protein-carbohydrate interactions are directly /Df(2L)ED611 (M) males in each of four replicates is shown.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that saccharide chains of the egg coats play pivotal roles in the induction of acrosome reaction, but their structures remain to be determined except for some echinoderms (for reviews see Miller and Ax, 1990;Litscher and Wassarman, 1993;Mengerink and Vacquier, 2001). In these animals, a very long sulfated linear polysaccharide chain plays a key role in the induction of acrosome reaction and the sperm seem to recognize the highly ordered spatial arrangement of the sulfate moieties (Hoshi et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It involves the exocytosis of the acrosomal vesicle to expose the devices for penetration through the egg coats and for subsequent fusion with the egg plasma membrane (Longo, 1997). Although it is well established that the egg coat contains signal molecules for the induction of acrosome reaction, our knowledge on the chemical structure of such molecules is much limited except for some echinoderms (for reviews see Miller and Ax, 1990;Litscher and Wassarman, 1993;Mengerink and Vacquier, 2001). In sea urchins, egg jelly polysaccharides such as the fucose sulfate polymer (FSP) (Vacquier and Moy, 1997;Alves et al , 1997Alves et al , , 1998VilelaSilva et al ., 1999) plays a key role for the induction of acrosome reaction though some other jelly components are involved in the induction (Yamaguchi et al ., 1987;Hirohashi and Vacquier, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Linear polymers of ␣-L-1,3-sulfofucose are only known in echinoderms (10), the single invertebrate phylum leading to the evolution of vertebrates (29). In addition to egg jelly coats, these polymers are also found in the extracellular matrix of the adult body wall in echinoderms (30).…”
Section: Discussionmentioning
confidence: 99%